1999
DOI: 10.1007/s002130050875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of central and peripheral nicotinic blockade on human nicotine discrimination

Abstract: Nicotine produces interoceptive stimulus effects in humans, which may be critical in understanding tobacco use. It has not yet clearly been demonstrated that discrimination of nicotine, or any drug, in humans is due to its central effects. We compared effects of mecamylamine (10 mg p.o.), a central and peripheral nicotine antagonist, on nicotine discrimination with those of trimethaphan (10-40 microg/kg per min i.v.), a peripheral nicotine antagonist only, and placebo. Smokers (n = 6) were first trained to rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Similarly, in six participants that had learned to discriminate caffeine, triazolam shifted the dose-effect curve for percent drug-appropriate responding rightward (Oliveto et al, 1997). In another study, the cholinergic antagonist mecamylamine attenuated the discriminative-stimulus effects and some of the subject-rated effects of nicotine in the same number of participants (Perkins et al, 1999). The positive results from those studies, as well as the present results, suggest that this sample size is suitable for detecting an antagonism of the behavioral effects of a stimulant.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similarly, in six participants that had learned to discriminate caffeine, triazolam shifted the dose-effect curve for percent drug-appropriate responding rightward (Oliveto et al, 1997). In another study, the cholinergic antagonist mecamylamine attenuated the discriminative-stimulus effects and some of the subject-rated effects of nicotine in the same number of participants (Perkins et al, 1999). The positive results from those studies, as well as the present results, suggest that this sample size is suitable for detecting an antagonism of the behavioral effects of a stimulant.…”
Section: Discussionsupporting
confidence: 64%
“…The number of subjects enrolled was based on power calculations from previous studies using nearly identical methods (Rush et al, 2003. In addition, a sample size of seven participants is consistent with prior drug-discrimination studies in humans in which drug pretreatments or combinations were administered in an attempt to modify the discriminativestimulus effects of a stimulant (eg Hart et al, 2002;Lile et al, 2004;Oliveto et al, 1997;Perkins et al, 1999;Rush et al, 2003Rush et al, , 2004. In our previous studies with alprazolam and risperidone, a significant attenuation of the discriminativestimulus and some of the positive subject-rated effects of the higher doses of D-amphetamine was observed with six and eight subjects, respectively (Rush et al, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only two published studies in which the discriminative-stimulus and self-reported effects of a stimulant drug were assessed after pretreatment with an antagonist (Oliveto et al, 1997;Perkins et al, 1999). In the first study, six participants were trained to discriminate between caffeine (320 mg/70 kg) and placebo (Oliveto et al, 1997).…”
Section: D-amphetamine and Risperidone In Humansmentioning
confidence: 99%
“…Triazolam did not significantly attenuate these self-reported effects of caffeine. In the second study, six smokers were trained to discriminate between 20 g/kg intranasal nicotine and placebo (Perkins et al, 1999). A range of doses of nicotine (0, 3, 6, 12, and 20 g/kg) was then tested alone and after pretreatment with mecamylamine (10 mg p.o.…”
Section: D-amphetamine and Risperidone In Humansmentioning
confidence: 99%
“…It produces interoceptive and discriminative stimuli, and some cross-generalization between nicotine and other addictive drugs has been found (Brioni et al, 1997;Perkins et al, 1999;Cohen et al, 2002). Chronic tobacco use in humans or chronic administration of nicotine in rodents generally results in a state of "physical dependence" characterized by the occurrence of a withdrawal syndrome (Hughes et al, 1994;Malin, 2001).…”
mentioning
confidence: 99%